The one-to-one functions g and h

are defined as follows.

G {(−8, 7), (−5,- 6),(0, -8),( 7, 3)}

H(x)=3x+4

sorry i didn't put the entire question the first time.

Find the following:

G^-1(-8)=

H^-1(x)=

(h∘h^−1)(−8)

G^{-1}(-8)= 0

y =3x+4

3x= (y-4)

x=(y-4)/3

H^{-1}(x)=(x-4)/3

(h∘h^{−1})(x)= h((x-4/3)= 3((x-4)/3)+4=x

(h∘h^{−1})(−8)= -8

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up